Learning Mathematical Logic and Sets Using E-Learning - Syariful Fahmi; Soffi Widyanesti Priwantoro (Quality Assurance Institute (LPM) State Islamic University Walisongo Semarang, 2023)
Video is a learning medium that is simple to integrate into a variety of activities, both online and offline. As a result, video development, including studying mathematical logic and set material, is essential. This research aims to develop project-based educational videos on mathematical logic and mathematics material. This research is development research using the Richey Klein (DPE) development model. There are three stages of development: design, production, and evaluation. This educational video was implemented on 25 students in the third semester of the Mathematics Education Study Program (FKIP UAD). The results of the material expert assessment showed a score of 4.23 (good category) and the media expert assessment scored 4.55 (very good category). Besides that, the student’s response during implementation got a score of 3.9 (good category).